Corrosion and fouling control in desalination industry - Saji, Viswanathan S.; Meroufel, Abdelkader A.; Sorour, Ahmad A. (Springer, 2020)
This book addresses two critical problems that plague materials that make up components in both desalination and cooling water systems: corrosion, and fouling. The book addresses various types and components of industrial desalination technologies with solutions for controlling corrosion, scaling and biofouling. Issues unique to desalination systems, vital for the production of clean water, are considered as well. Green technologies are discussed throughout, along with environmental and economic considerations. The book presents solutions to the problems encountered by internal and external parts of these systems and will aid professionals that design, operate, and maintain them. It will be valuable to professionals in the materials, corrosion, electrochemical and wastewater industries, as well as chemical engineers. Addresses the corrosion issues facing the conventional and modern water desalination systems; Discusses the causes and remediation of problems caused by corrosion, scaling, and biofouling in water treatment; Offers green solutions, thereby minimizing environmental impact while increasing control and productivity of water systems; Suitable for professionals working with water desalination plants, materials scientists and corrosion engineers.
Includes index.
Keywords: Corrosion and anti-corrosives.; Fouling.; Saline water conversion.; elektronické knihy; electronic books